2012
DOI: 10.1289/ehp.1104031
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Environmental Health Research in the Arabian Middle East: Lessons Learned and Opportunities

Abstract: Background: The Arabian Gulf nations are undergoing rapid economic development, leading to major shifts in both the traditional lifestyle and the environment. Although the pace of change is brisk, there is a dearth of environmental health research in this region.Objective: We describe challenges and successes of conducting an environmental epidemiologic study in the United Arab Emirates (UAE), a Gulf nation in the Middle East, with an inter-disciplinary team that includes in-country academic and government col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…As pointed out by Yeatts et al (2012), the scientific interests in environmental health research are for many factors including the rapid transformation in the physical environment associated with raises in industry and traffic-related pollutants, extremely high temperatures and alterations in lifestyles. They concluded that, despite the accelerated and dramatic environmental changes, the environmental health-related research was little (Yeatts et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out by Yeatts et al (2012), the scientific interests in environmental health research are for many factors including the rapid transformation in the physical environment associated with raises in industry and traffic-related pollutants, extremely high temperatures and alterations in lifestyles. They concluded that, despite the accelerated and dramatic environmental changes, the environmental health-related research was little (Yeatts et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…As pointed out by Yeatts et al (2012), the scientific interests in environmental health research are for many factors including the rapid transformation in the physical environment associated with raises in industry and traffic-related pollutants, extremely high temperatures and alterations in lifestyles. They concluded that, despite the accelerated and dramatic environmental changes, the environmental health-related research was little (Yeatts et al 2012). Similar to the previous finding, the global research report by Thomson Reuters indicated that during the period from 2005 to 2009, the region of the Middle East (Persian, Arabian and Turkish Middle East) published only 4676 documents in environment/ecology research which represent a proportion equal to 3.24% of total world's research productivity (Adams et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies about public health situation, challenges and future aspects of health systems in Arab countries have been published [55][56][57]. Similarly, several studies in environmental and occupational health risks in Arab countries have also been published [58][59][60][61][62][63]. However, up to the authors' best knowledge, no reports about the quantity and quality of public, environmental and occupational health from Arab countries had been published [64][65][66][67].…”
Section: Introductionmentioning
confidence: 99%
“…This situation limits certain study designs and testing of the hypotheses. Scientists also often face challenges of quality control when projects are conducted in another country (11, 12). Although most investigators seek to be in the field when the study is initiated and to visit the field often and periodically, it is difficult to make frequent and prolonged visits to provide constant supervision.…”
Section: Introductionmentioning
confidence: 99%